Implementation of “Direct vs Indirect License”: A Comparative Study of Music Licensing Systems between Indonesia and the United States of America - Fattah, Ade Syaifullah; Wahyuni, Ridha (Universitas Islam Sultan Agung, 2025)
This study examines the implementation of direct and indirect license systems in copyright royalty management, particularly in the music sector, by comparing the regulatory frameworks of Indonesia and the United States. In Indonesia, copyright royalties are predominantly managed through a collective licensing system via LMK (Collective Management Organizations) and LMKN (National Collective Management Organization). Although the legal framework permits licensing directly between creators and users, the lack of explicit regulation on direct licenses creates legal uncertainty and risks overlapping claims. In contrast, the United States recognizes and regulates direct licenses under the Copyright Act of 1976, allowing copyright owners to manage their economic rights independently or through Performing Rights Organizations such as ASCAP, BMI, and SESAC. This legal certainty enables greater flexibility, negotiation power, and transparency for creators and industry stakeholders. The study employs a normative-empirical legal method, combining statutory analysis with interviews, to explore how Indonesia might benefit from clearer legal provisions to support a dual licensing approach. Strengthening legal clarity on direct licensingcould ensure fairness, legal certainty, and adaptability for both creators and music industry actors in Indonesia’s growing creative economy.